Answers

  • Brainly User
2016-01-28T08:09:18+08:00
X + y = 61
      y = 61 - x

Representation:
  Smaller number: x
  Larger number:  61-x

Condition:  Three times the smaller is 13 less than the larger.

Equation:
   3x = (61-x) - 13
   3x = 61 - 13 - x
   3x + x = 61-13
   4x = 48
   4x/4 = 48/4
   x = 12
  
Substitute 12 for x:
   Smaller number: x = 12
   Larger number: 61- 12 =  49

ANSWER:The numbers are 12 (smaller number) and 49 (larger number).

Check:
The sum of two numbers is 61.
   12 + 49 = 61
           61 = 61  (True)

Three times the smaller number is 13 less than the larger number
    3 (12)  = 49 - 13
    36 = 36                      (True) 

0